Just sentencing : principles and procedures for a workable system - Frase, Richard S. (Studies in penal theory and philosophy., 2013)
This title presents a fully developed punishment theory which incorporates both utilitarian and retributive sentencing purposes. The author describes and defends a hybrid sentencing model that integrates theory and practice - blending and balancing both the competing principles of retribution and rehabilitation and the procedural concern of weighing rules against discretion.